Pemberdayaan Ekonomi Desa Jati Melalui Produksi dan Pemasaran Sirup Rempah - Hikmawati, Hanifah; Sudarmi, Sri (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The "Economic Empowerment of Jati Village through Production and Marketing of Spice Syrup" program aims to utilize the potential of local spices as an economic resource that can improve the welfare of village communities. Jati Village, with its wealth of spices such as ginger, turmeric and ginger, has a great opportunity to develop spice syrup products of high quality and high selling value. This program is implemented in several stages. First, identification and analysis of the potential of spices and community training needs were carried out. Furthermore, intensive training was carried out regarding spice syrup making techniques, quality control, as well as marketing and business management strategies. The results of this program are expected to empower the people of Jati Village by increasing income through the production of spice syrup, creating employment opportunities, and preserving the tradition of using local spices. In addition, this program aims to expand public knowledge about the economic and health benefits of spices, as well as strengthening the competitiveness of local products in the market. The impact of this training is the innovation of spice syrup to be used as mixed ice in the "Es Kang Bejo" business.